Drying of Quaternary Coatings Of Poly(Styrene) and Poly(Methyl Methacrylate) - Prashar, Anubhav (My University, 2018)
Gravimetric study of quaternary polymeric coatings has been investigated. The effect of various coating parameters, i.e., initial thickness and coating composition has been studied. Two quaternary systems: poly(styrene) – ethylbenzene – toluene – p-xylene and poly(methyl methacrylate) – ethylbenzene – toluene – acetone, have been studied. Their residual solvent, average concentrations of polymer, solvent and coating thickness have been compared with binary and ternary coatings. The results indicate that the amount of any costly solvent can be decreased to significant value in quaternary coating by using other cheaper solvents, which give nearly same drying rate and, hence, lowers the energy requirement for the drying. Binary coatings of poly(styrene) – toluene, poly(styrene) – ethylbenzene, poly(styrene) – p-xylene, poly(methyl methacrylate) – toluene, poly(methyl methacrylate) –ethylbenzene, and poly(methyl methacrylate) – acetone has been compared with corresponding quaternary systems.Ternary coatings of poly(styrene) – toluene – ethylbenzene, poly(styrene) – toluene –p-xylene, poly(styrene) – ethylbenzene – p-xylene, poly(methyl methacrylate) – toluene – acetone, poly(methyl methacrylate) – toluene – ethylbenzene, and poly(methyl methacrylate) E– ethylbenzene – acetone has been compared with corresponding quaternary systems.
Keywords: Drying of quaternary coatings; Residual solvent; Thin films; Use of solvents blends